A study on noise environment in the teaching and learning process in University classrooms / Hazry Haqimi Rohaizad and Mohamad Haszirul Mohd Hashim - Rohaizad, Hazry Haqimi; Mohd Hashim, Mohamad Haszirul (2023)
The purpose of this study is to examine the relationship between classroom noise and student learning. This research is a quantitative and qualitative case study. The actual study is carried out and data gathered by giving questionnaires to respondents made up of 40 students who participated in the case study and by starting an experiment in a university lecture hall. Study data was evaluated by using Microsoft Excel from Microsoft Office 2023. The study identifies noise levels in university classrooms during academic hours and determines student satisfaction in academic classrooms. The results of the analysis are presented in the form of data from the experiment and the total number of respondents. According to the study's findings, noise can interfere with the process of teaching and learning in university buildings and classrooms. This study is significant because it may be used to determine the best ways to develop a workshop to improve teaching effectiveness and student learning. Additionally, it is anticipated that this study will serve as a model for additional research.